Leader gene identification for digestive system cancers based on human subcellular location and cancer-related characteristics in protein–protein interaction networks - Chen, Hongwei; Rong, Zherou; Ge, Luanfeng; Yu, Hongzheng; Li, Chao; Xu, Manyi; Zhang, Zihan; Lv, Junjie; He, Yuehan; Li, Wan; Chen, Lina (Frontiers in Genetics, 2022)
Stomach, liver and colon cancers are the most common digestive system cancers leading to mortality. Cancer leader genes are the genes that contribute to tumor initiation and could shed light on the molecular mechanisms in tumorigenesis. In the present work, we proposed an integrated procedure for identifying cancer leader genes based on subcellular location information and cancer-related characteristics considering the effects of nodes on their neighbors in human protein-protein interaction networks. A total of 69, 43 and 64 leader genes were identified for stomach, liver and colon cancer, respectively. Further literature review, protein expression level and independent datasets all verified their association with corresponding cancer types. These final leader genes were expected to be used as diagnostic biomarkers and targets for new treatment strategies. The procedure for identifying cancer leader genes could be expanded to open up a window into the mechanisms, early diagnosis and treatment of other cancer types.